Developing AI-Integrated E-Pop Up Book Media for Enhancing Vocabulary Interpretation for Elementary Students - Maulana, Arza; Purwati, Panca Dewi (JOLLT Journal of Languages and Language Teaching, 2025)
This research started from the problem of low learning outcomes in interpreting the vocabulary of grade IV students in the Indonesian subject. Interpreting vocabulary is very difficult for students because of the large number of vocabulary in Indonesian and the lack of use of learning media in the classroom. In addition, there is a lack of interest in learning because teachers are not able to use learning media that are in accordance with the characteristics of grade IV students. Therefore, AI-based e-pop up book media can help students interpret vocabulary. From these problems, this study aims to describe e-pop up book media, describe the results of the feasibility test of e-pop up book media, and describe the results of the effectiveness test of e-pop up book media. This research method uses R&D research with the development of the Borg and Gall model which was carried out up to stage 8 only due to time and cost limitations with a sample of 35 students. The media created is then tested by material and media experts. The results of the media feasibility test were obtained from assessments according to material experts of 95% (very feasible) and according to media experts of 92.5% (very feasible). The study found that AI-integrated e-pop up books significantly improved students' vocabulary interpreting skills, with a t-test result of 17,791 and an N-gain score of 0.7084 (high category). Based on the results of the study, it shows that the use of artificial intelligence-based e-pop up book media is very effective in improving learning outcomes in interpreting elementary school grade IV vocabulary.Â 